Comparative study on grey matter structure MRI between amyotrophic lateral sclerosis patients with limb-onset and bulbar-onset - SHEN Dong-chao; ZOU Peng; HOU Bo; YANG Xun-zhe; LIU Ming-sheng; CUI Li-ying (Chinese Journal of Contemporary Neurology and Neurosurgery, 2022)
Objective To compare the differences between the gray matter structures of amyotrophic lateral sclerosis (ALS) patients with limb-onset and bulbar-onset. Methods A total of 35 ALS patients with normal cognitive function were enrolled in Peking Union Medical College Hospital ALS Registry Platform from September 2013 to March 2018, and 20 healthy controls with matched age and education were included in the study. ALS patients were divided into limb-onset group (ALS-L group, n = 20) and bulbar-onset group (ALS-B group, n = 15) according to their clinical onset sites. Three-dimensional T1-fast spoiled gradient-recalled (3D-T1-FSPGR) of all subjects was collected. Gray matter volume of each group were compared using voxel-based morphometry (VBM). Within the compound region of interest (ROI) consisting of bilateral primary motor cortex, premotor cortex and supplementary motor area, the atrophy patterns of the motor cortex were compared between ALS-L group and ALS-B group. Results Compared with the control group, the ALS-L group had decreased gray matter volume in the left superior temporal gyrus-temporal pole (t = 3.932, uncorrected P < 0.001), left middle temporal gyrus (t = 3.836, uncorrected P < 0.001), right insula (t = 3.992, uncorrected P < 0.001). Compared with the ALS-B group, the ALS-L group had decreased gray matter volume in the right superior frontal gyrus (t = -3.158, uncorrected P < 0.001), left cingulate gyrus (t = -3.002, uncorrected P < 0.001). In the analysis of the motor cortex as ROI, the gray matter volume of the segments representing hand (t = 2.237, uncorrected P < 0.001) and lower limb (t = 2.728, uncorrected P < 0.001) of the left motor cortex in the ALS-L group was reduced significantly than that of ALS-B group. Conclusions ALS-L has more significant gray matter atrophy than ALS-B, and the local atrophy pattern of motor cortex in ALS patients corresponds to its functional disability.